Effect of long-term storage on degradation of 21 phenolic compounds in green tea - Kalendová, Petra; Meloun, Milan; Česlová, Lenka (University of Pardubice, 2020)
The storage resistance of 21 selected phenolic compounds present in ten samples of commercially available green tea was monitored using the HPLC/MS/MS over a 16 weeks period using multivariate statistical analysis to compare the different types of packaging. The HPLC/MS/MS method with the computer-aided analysis enabled the fast evaluation of the long-time storage resistance of valuable compounds present in green tea, yielding useful information to customers about their degradation, which affected the sensory properties of the green tea, such as taste and colour. An explanatory data analysis provided an initial visualization of the multivariate data matrix while a factor analysis, hierarchical cluster analysis and discriminant analysis enabled the classification of the green tea samples into clusters according to the storage resistance of the compounds of interest. A significant reduction in the content of all monitored compounds was indicated after 3 weeks of storage, which was also found to be dependent on the type of packaging used. The samples in a plastic box were more stable during long-time storage in comparison to the samples in a paper box.
Vliv dlouhodobého skladování na degradaci 21 fenolických látek v zeleném čaji
Keywords: green tea; long-term storage; phenolic compounds; packages of green tea; HPLC/MS/MS; zelený čaj; dlouhodobé skladování; fenolické látky; balení zeleného čaje; HPLC/MS/MS